Spatio-temporal dynamics of undisturbed macroinvertebrate communities in the Mondego River basin : contribution to the ecological assessment of streams - Chaves, Maria Luísa Correia, 1975- (2008)
Tese de doutoramento em Biologia (Ecologia), apresentada à Universidade de Lisboa através da Faculdade de Ciências, 2008